2020
DOI: 10.4012/dmj.2019-221
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity evaluation of eluates from universal adhesives by real-time cell analysis

Abstract: The aim of this study was to evaluate the cytotoxicity of universal adhesives on L929 mouse fibroblast cell line by using a realtime cell analysis. In order to obtain extract, six different cured dental adhesives were immersed in Dulbecco's Modified Eagle's Medium (DMEM) at 37°C for 24 h. A real-time cell analysis system was used to assess cytotoxicity of the dental adhesives. After seeding 25,000 cells/300 μL/well cell suspensions into the wells of an e-plate, fibroblasts were exposed to extracts of tested ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…This result may be due to the effect of the CDHP being added to the MTA cement. L929 cells were observed to be elongated into a spindle shape with a size of about 100 μm, which is a typical morphology of L929 as an adhesive cell 22) . Elliott et al 17,18) also reported a decrease in cell viability above a certain level with increasing CDHP concentrations, but no decrease in cell viability was observed in the 0.2-0.8 g/mL range in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…This result may be due to the effect of the CDHP being added to the MTA cement. L929 cells were observed to be elongated into a spindle shape with a size of about 100 μm, which is a typical morphology of L929 as an adhesive cell 22) . Elliott et al 17,18) also reported a decrease in cell viability above a certain level with increasing CDHP concentrations, but no decrease in cell viability was observed in the 0.2-0.8 g/mL range in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, these methods cannot meet the needs of high-throughput data analysis because of the cumbersome relevant statistical analysis [ 6 ]. In order to solve these problems, researchers have proposed a new approach that can provide detailed information on the entire lifecycle of cells by observing and tracking them in real-time and in situ [ [7] , [8] , [9] ]. This method not only greatly deepens our understanding of the physiological properties of cells but can also accelerate drug development processes as it allows us to assess drug cytotoxicity directly and rapidly [ 3 ].…”
Section: Introductionmentioning
confidence: 99%